The earlier metabolic bariatric surgery is performed, the better expected clinical benefit beyond weight loss: a short-term follow-up study - Wenxing Gao; Qian Li; Rui Zhang; Xiao Wu; Qian Suo; Gang Ji (European Journal of Medical Research)
Abstract Background Obesity is a global public health challenge, which is strongly associated with dozens of diseases. Metabolic bariatric surgery is recognized as a long-term and effective treatment for obesity and obesity-related medical conditions. The aim of this study is to investigate the relationship between the timing of metabolic bariatric surgery and postoperative weight loss along with the clinical remission of obesity-related medical conditions. Methods This study examined 143 patients with obesity who underwent laparoscopic sleeve gastrectomy (LSG) from Feb 2015 to Feb 2022. The median time from meeting the criteria for metabolic bariatric surgery to finally undergoing metabolic bariatric surgery for all participants was 5.75 years. Based on this, the participants were divided into two groups: the early operation group (persons with a duration of obesity prior to surgery of less than 5 years) and the late operation group (those with the duration of longer than 5 years). Weight metrics, biochemical indicators and improvements in obesity-related medical conditions of both groups were analyzed before the operation and 1 year after the operation. Results All patients completed a postoperative follow-up of at least 1 year. There was no significant variation in weight loss, TWL% (P ≥ 0.05) between the early operation and late operation groups. Whereas patients in the early operation group had better improvements in obesity-related medical conditions 1 year after surgery (P < 0.05). Furthermore, the early operation group showed a more pronounced decrease in related metabolic indices, such as fasting blood glucose and triglyceride (P < 0.01). Conclusions Patients undergoing metabolic bariatric surgery experienced significant weight reduction. Notably, those in the early operation group exhibited better improvement in obesity-related medical conditions and related metabolic indices post-operation.